THE ROLE OF TRAINING METHODS AND MOTOR ABILITY IN DEVELOPING FOOTBALL DRIBBLING SKILLS - Yose Fakhri; Masrun; Khairuddin; Ali Mardius; Aldo Naza Putra; Khalid Rijaluddin (Curricula: Journal of Teaching and Learning, 2026)
Study This aim For analyze influence exercise fun games and zig-zag dribble as well as ability motor ability ( motor ability ) towards agility of dribbling the ball in players Porsepa FC Subdistrict Lareh Sago Halaban , Lima Puluh Kota Regency . Research design use design factorial 2 x 2 with treatment in the form of method exercise as variables free , ability motor as variables attributes , and agility in dribbling the ball as variables bound . Population study is all over player football consists of 32 people, who at the same time made into sample through technique total sampling . Data collected use test ball dribbling agility and test ability motor , then analyzed with two-way ANOVA test path (2 x 2). Research results show that : (1) practice fun games produce greater agility in dribbling the ball tall compared to exercise zig-zag dribble (p = 0.000 < α = 0.05); (2) no there is difference significant between ability motor high and low to dribbling agility (p = 0.825 > α = 0.05); (3) there is interaction significant between method training and skills motor to ball dribbling agility (p = 0.001 < α = 0.05); (4) in the group with ability motor height , exercise fun games more effective compared to zig-zag dribble (p = 0.000 < α = 0.05); (5) in group with ability motor low , no there is difference between second method exercise (p = 0.494 > α = 0.05); (6) exercise fun games show difference agility of dribbling the ball between ability motor high and low (p = 0.034 < α = 0.05); and (7) exercise zig-zag dribble also shows difference agility of dribbling the ball between ability motor high and low (p = 0.043 < α = 0.05). In overall , research This confirm that method exercise fun games more effective in increase agility in dribbling the ball, especially in players with ability motor high , and there is interaction significant between method training and skills motor to results agility in dribbling the ball